Synthesis of 1-indanones with a broad range of biological activity - Turek, Marika; Szczęsna, Dorota; Koprowski, Marek; Bałczewski, Piotr (Beilstein Journal of Organic Chemistry, 2017)
This comprehensive review describes methods for the preparation of 1-indanones published in original and patent literature from 1926 to 2017. More than 100 synthetic methods utilizing carboxylic acids, esters, diesters, acid chlorides, ketones, alkynes, alcohols etc. as starting materials, have been performed. This review also covers the most important studies on the biological activity of 1-indanones and their derivatives which are potent antiviral, anti-inflammatory, analgesic, antimalarial, antibacterial and anticancer compounds. Moreover, they can be used in the treatment of neurodegenerative diseases and as effective insecticides, fungicides and herbicides.
Keywords: biological activity; Diels–Alder reaction; Friedel–Crafts reaction; 1-indanones; Nazarov reaction